2022
DOI: 10.1038/s41598-022-05687-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 pandemic on neuropsychiatric symptoms in dementia and carer mental health: an international multicentre study

Abstract: As a global health emergency, the rapid spread of the novel coronavirus disease (COVID-19) led to the implementation of widespread restrictions (e.g., quarantine, physical/social distancing measures). However, while these restrictions reduce the viral spread of COVID-19, they may exacerbate behavioural and cognitive symptoms in dementia patients and increase pressure on caregiving. Here, we aimed to assess the impact of COVID-19 and related restrictions on both carers and people living with dementia across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
(53 reference statements)
0
23
0
4
Order By: Relevance
“…( Alzheimer Society, n.d. Risk factors for dementia (2022) ; Alzheimer's Disease International (2022) ; Canevelli et al (2020) ; Carbone et al (2021) ; Clare et al (2022) ; Giebel et al (2021) ; Hernández-Ruiz et al (2021) ; Li et al (2022) ; Mayo Clinic (2022) ; Noguchi et al (2021) ; Özgün-Başıbüyük et al (2021) ; Prince Martin et al (2015) ; Rongwei et al (2010) ; Sutton et al (2022) ; Wei et al (2022) ; World Health Organization (2022)…”
Section: Uncited Referencesmentioning
confidence: 99%
“…( Alzheimer Society, n.d. Risk factors for dementia (2022) ; Alzheimer's Disease International (2022) ; Canevelli et al (2020) ; Carbone et al (2021) ; Clare et al (2022) ; Giebel et al (2021) ; Hernández-Ruiz et al (2021) ; Li et al (2022) ; Mayo Clinic (2022) ; Noguchi et al (2021) ; Özgün-Başıbüyük et al (2021) ; Prince Martin et al (2015) ; Rongwei et al (2010) ; Sutton et al (2022) ; Wei et al (2022) ; World Health Organization (2022)…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Some research has already investigated this to an extent; a rapid review of evidence related to the impact of COVID-19 isolation measures on mental health among people with dementia found that most studies identified worsening behavioral and psychological symptoms of dementia (BPSD) (28). Some of the research found these results through subjective assessments made by caregivers (29), qualitative interviews of people with dementia and their caregivers (30,31), and across international contexts (32).…”
Section: Introductionmentioning
confidence: 99%
“…Bretonniere et al found that the duration of confinement and increased stress of caregivers significantly correlate with the severity of neuropsychiatric symptoms [ 5 ]. Besides, limited understanding of the COVID-19 situation and lack of outpatient rehabilitation services are also associated with a deterioration of neuropsychiatric symptoms [ 114 , 116 ]. Apart from the aforementioned studies completed after 1–2 months of COVID-19 lockdown, Chen et al reported a longitudinal 1-year follow-up study comparing cognitive function of AD patients before and after COVID-19 lockdown to determine the long-term impact of confinement on AD patients.…”
Section: Covid-19 and Admentioning
confidence: 99%